2018
DOI: 10.1002/dev.21630
|View full text |Cite
|
Sign up to set email alerts
|

Physiological linkage and affective dynamics in dyadic interactions between adolescents and their mothers

Abstract: This study examined physiological linkage (specifically, linkage in respiratory sinus arrhythmia; RSA) between parents and youth (aged 11-17) across conflict and fun activity discussion tasks. We also examined whether observed, momentary negative affect or parental depressive symptoms, would moderate patterns of RSA linkage across the interaction tasks. RSA linkage was assessed using a multilevel actor-partner interdependence model (APIM). Participants were 59 mother-adolescent dyads, including mothers with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 47 publications
1
59
1
Order By: Relevance
“…Although no differences in physiological synchrony were observed as a function of the child's sex in the current study, some research has reported different patterns of RSA in mothers interacting with daughters relative to mothers interacting with sons (McKillop & Connell, 2018). Furthermore, although the present study did not examine how children's overall levels of RSA were associated with their prosocial empathy, some research has found that such associations are moderated by sex, with associations in opposite directions for boys relative to girls (Eisenberg, Fabes, Karbon, et al, 1996).…”
Section: Limitations and Future Directionscontrasting
confidence: 91%
See 2 more Smart Citations
“…Although no differences in physiological synchrony were observed as a function of the child's sex in the current study, some research has reported different patterns of RSA in mothers interacting with daughters relative to mothers interacting with sons (McKillop & Connell, 2018). Furthermore, although the present study did not examine how children's overall levels of RSA were associated with their prosocial empathy, some research has found that such associations are moderated by sex, with associations in opposite directions for boys relative to girls (Eisenberg, Fabes, Karbon, et al, 1996).…”
Section: Limitations and Future Directionscontrasting
confidence: 91%
“…In that study, dyads with no history of maternal depression evidenced positive physiological synchrony during a negative discussion task, whereas dyads in which the mother did have a history of major depression showed negative physiological synchrony. Somewhat similar findings were observed in a study of adolescents (ages 11 to 17), which found evidence of positive timelagged physiological synchrony (over 15-s segments) across a positive and negative discussion task among dyads with no maternal history of depression, and attenuated synchrony among dyads with a history of maternal depression (McKillop & Connell, 2018).…”
Section: Phys Iolog Ic Al Syn Chronysupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, dyads with clinically depressed adolescents showed significant within‐person concordance whereby their physiological and behavioral responses became simultaneously dysregulated. In both preadolescent–mother and adolescent–mother dyads, maternal depressive symptoms are associated with disrupted RSA synchrony during conflictual discussions (Mckillop & Connell, ; Woody, Feurer, Sosoo, Hastings, & Gibb, ). Mothers experiencing greater depressive symptoms also show greater stability in RSA (Amole, Cyranowski, Wright, & Swartz, ; Mckillop & Connell, ) and negative emotion expressions (Connell, McKillop, Patton, Klostermann, & Hughes‐Scalise, ) during such discussions with adolescents, which suggests low physiological and emotional preparedness to respond to environmental or social stressors.…”
Section: Review Of Parent–adolescent Dyads As Temporal Interpersonal mentioning
confidence: 99%
“…Whether or not physiological synchrony reflects adaptive interpersonal processes depends on several factors including the domain of physiological responding and context (Timmons, Margolin, & Saxbe, 2015). Although RSA synchrony may be a feature of conflict dynamics in nondepressed parent-adolescent dyads (Mckillop & Connell, 2018;Woody et al, 2016), concordance of cortisol slopes indicating heightened stress in day-to-day life is a feature of dyads at risk for depression (LeMoult, Chen, Foland-Ross, Burley, & Gotlib, 2015). Specifically, dyads at risk for depression show elevated cortisol responses throughout the day compared to dyads not at risk and also show greater synchrony.…”
Section: Emotion Dynamics and Psychosocial Adjustment (Paths C1 And C2)mentioning
confidence: 99%